Bioisosteric substitution of adamantane with bicyclic lipophilic groups improves water solubility of human soluble epoxide hydrolase inhibitors. Issue 18 (15th September 2020) - Burmistrov, Vladimir; Morisseau, Christophe; Karlov, Dmitry; Pitushkin, Dmitry; Vernigora, Andrey; Rasskazova, Elena; Butov, Gennady M.; Hammock, Bruce D.
Graphical abstract: Highlights: Ureas with bicyclic lipophilic groups were studied as sEH inhibitors. 24 ureas with bicyclic lipophilic groups were synthesized. Bicyclic ureas 10-fold more soluble than the ureas containing adamantyl or aromatic groups. Effect of stereochemistry on sEH inhibitory activity was shown. Abstract: A series of inhibitors of the soluble epoxide hydrolase (sEH) containing lipophilic groups of natural origin (camphanyl, norcamphanyl, furan-2-yl) were developed. Inhibitory potency ranging from 0.4 nM to 2.16 μM were obtained. While having the same level of inhibitory activity bicyclic ureas are up to 10-fold more soluble than the corresponding ureas containing adamantyl or 4-trifluoromethoxyphenyl substituents. This makes them easier to formulate, more bioavailable and thus more promising as therapeutic sEH inhibitors. Endo / exo -form of compound 2b derived from l -camphor is 14-fold more potent than the corresponding analogue derived from d -camphor (IC50  = 3.7 nM vs. 50.6 nM) indicating enantiomeric preference.